Valuing EQ-5D-Y: the current state of play - N. Devlin; T. Pan; S. Kreimeier; J. Verstraete; E. Stolk; K. Rand; M. Herdman (Health and Quality of Life Outcomes, 2022)
Abstract Background For nearly a decade, value sets for the EQ-5D-Y were not available, reflecting challenges in valuing child HRQoL. A methodological research programme led to publication of a valuation protocol in 2020, which was rapidly taken up by local study teams. By the end of 2022, between 11 and 17 EQ-5D-Y value sets will be available, more than for any other child HRQoL measure. It is timely to review the experience of those using the protocol to identify early learnings and remaining issues where more research is needed. Methods In June 2021, the EuroQol Group organised a three-day workshop, bringing together all those involved in EQ-5D-Y value set studies and related methodological research concerning EQ-5D-Y and valuation. Workshop discussions were captured by note taking and recording all sessions and online chat. A narrative summary of all sessions was produced and synthesised to identify points of agreement and aspects of methods where uncertainty remains. Results There was broad agreement that DCE is working well as the principal valuation method. However, the most appropriate means of anchoring the latent scale values produced by DCE remains unclear. Some studies have deviated from the protocol by extending the number of states included in TTO tasks, to better support modelling of DCE and TTO. There is ongoing discussion about the relative merits of alternative variants of TTO and other methods for anchoring. Very few studies have consulted with local end-users to gauge the acceptability of methods used to value EQ-5D-Y. Conclusions Priority areas for research include testing alternative methods for anchoring DCE data; exploring the preferences of adolescents; and scale differences in values for EQ-5D-Y and adult EQ-5D states, and implications of such differences for the use of EQ-5D-Y values in HTA. Given the normative elements of the protocol, engaging with HTA bodies and other local users should be the first step for all future value set studies. Value sets undertaken to date are for the three-level EQ-5D-Y. However, the issues discussed in this paper are equally relevant to valuation of the five-level version of EQ-5D-Y; indeed, similar challenges are encountered valuing any measure of child HRQoL.